South Dravidian Languages: Consistent Null Subject or Discourse Pro-Drop? - A V, Arya Navya (International Journal of Linguistics, 2023)
Indian languages are not mentioned in any of the canonical literature on null subject languages as they do not fall in a specific subcategory neatly. They show a relatively consistent conjugation system, but have more features of Radical pro-drop languages than Consistent Null-Subject languages. (Note 1) I examine South Dravidian languages (henceforth SDLs), which show consistent conjugation system, much like the Romance languages yet drop arguments and adjuncts profusely, especially if they are once established in the discourse. There is a sense of hesitance amongst scholars to concede and group them among Radical pro-drop languages. I follow Sigurdsson (2011) in that generative literature has ‘misjudged the role of agreement for licensing and identifying of null arguments’(Sigurdsson, 2011, p. 276) and argue that the special nature of SDLs as radical pro-drop languages that have agreement prove to be a prime example of this. SDLs prove as prime examples to suggest a unified theory of pro in line with Barbosa (2019).